The First CNS-Active Carborane: A Novel P2X7 Receptor Antagonist with Antidepressant Activity - Wilkinson, S.; Gunosewoyo, Hendra; Barron, M.; Boucher, A.; McDonnell, M.; Turner, P.; Morrison, D.; Bennett, M.; McGregor, I.; Rendina, L.; Kassiou, M. (American Chemical Society, 2014)
Relative to other polycyclic frameworks (1-3), a carborane cage (4 and Cs·5) exerts a significant biological effect as an inhibitor of the purinergic P2X7 receptor (P2X7R) which allows one to target depression in vivo and thus demonstrate, for the first time, that a carborane has the capacity to modify CNS activity